2020
DOI: 10.1101/2020.10.16.343426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse viral proteases activate the NLRP1 inflammasome

Abstract: The NLRP1 inflammasome is a multiprotein complex that is a potent activator of inflammation. Mouse NLRP1B can be activated through proteolytic cleavage by the bacterial Lethal Toxin (LeTx) protease, resulting in degradation of the N-terminal domains of NLRP1B and liberation of the bioactive C-terminal domain, which includes the caspase activation and recruitment domain (CARD). However, a natural pathogen-derived effector that can activate human NLRP1 remains unknown. Here, we use an evolutionary model to ident… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Moreover, they found that live human rhinovirus, an enterovirus that causes the common cold, induced at least some NLRP1-dependent cytokine processing in primary human airway cells, although rhinovirus-induced cell death was entirely NLRP1 independent. A recent manuscript confirmed that enteroviral 3Cpros indeed cleave and activate hNLRP1 (Tsu et al, 2021). Overall, these manuscripts have identified the first pathogen-associated factor that activates hNLRP1, at least in experimental settings.…”
mentioning
confidence: 58%
“…Moreover, they found that live human rhinovirus, an enterovirus that causes the common cold, induced at least some NLRP1-dependent cytokine processing in primary human airway cells, although rhinovirus-induced cell death was entirely NLRP1 independent. A recent manuscript confirmed that enteroviral 3Cpros indeed cleave and activate hNLRP1 (Tsu et al, 2021). Overall, these manuscripts have identified the first pathogen-associated factor that activates hNLRP1, at least in experimental settings.…”
mentioning
confidence: 58%
“…For example, CARD8 and NLRP1 may have evolved to respond to different pathogens. Consistent with this idea, recent reports revealed that human rhinovirus 3C protease and HIV protease directly cleave and activate human NLRP1 and CARD8, respectively (Robinson et al, 2020;Tsu et al, 2020;Wang et al, 2020). Moreover, human NLRP1 was also recently reported to sense intracellular long doublestranded RNAs by directly binding them through its leucine-rich repeat (LRR) domain (Bauernfried et al, 2020), which is absent in CARD8.…”
Section: Discussionmentioning
confidence: 72%
“…The biological purposes of the NLRP1 and CARD8 inflammasomes have not yet been established (Bachovchin, 2021). Notably, NLRP1 is highly polymorphic, and an array of dissimilar pathogen-associated stimuli, including viral proteases and dsRNA, induce its activation in experimental systems (Hornung et al, 2009;Robinson et al, 2020;Tsu et al, 2020). Curiously, however, none of these stimuli universally activate all functional NLRP1 alleles in rodents and humans.…”
Section: Discussionmentioning
confidence: 99%
“…A wide array of unrelated pathogen-derived stimuli, including bacterial and viral proteases, E3 ligases, and long dsRNA, have been reported to activate at least one human or rodent NLRP1 allele via functional degradation (Table S1) (Boyden and Dietrich, 2006;Hornung et al, 2009;Robinson et al, 2020;Sandstrom et al, 2019;Tsu et al, 2020). The most well-studied of these is the anthrax lethal factor (LF) metalloprotease, which cleaves some rodent NLRP1 alleles near their N-termini and thereby generates unstable neo-N-termini that are rapidly recognized and degraded by the N-end rule proteasome degradation pathway (Chui et al, 2019;Frew et al, 2012;Sandstrom et al, 2019).…”
Section: Introductionmentioning
confidence: 99%